Transcriptional signatures regulated by TRPC1/C4-mediated Background Ca2+ entry after pressure-overload induced cardiac remodelling. (January 2021) - Camacho Londoño, Juan E.; Kuryshev, Vladimir; Zorn, Markus; Saar, Kathrin; Tian, Qinghai; Hübner, Norbert; Nawroth, Peter; Dietrich, Alexander; Birnbaumer, Lutz; Lipp, Peter; Dieterich, Christoph; Freichel, Marc
Abstract: Aims: After summarizing current concepts for the role of TRPC cation channels in cardiac cells and in processes triggered by mechanical stimuli arising e.g. during pressure overload, we analysed the role of TRPC1 and TRPC4 for background Ca 2+ entry (BGCE) and for cardiac pressure overload induced transcriptional remodelling. Methods and results: Mn 2+ -quench analysis in cardiomyocytes from several Trpc -deficient mice revealed that both TRPC1 and TRPC4 are required for BGCE. Electrically-evoked cell shortening of cardiomyocytes from TRPC1/C4-DKO mice was reduced, whereas parameters of cardiac contractility and relaxation assessed in vivo were unaltered. As pathological cardiac remodelling in mice depends on their genetic background, and the development of cardiac remodelling was found to be reduced in TRPC1/C4-DKO mice on a mixed genetic background, we studied TRPC1/C4-DKO mice on a C57BL6/N genetic background. Cardiac hypertrophy was reduced in those mice after chronic isoproterenol infusion (−51.4%) or after one week of transverse aortic constriction (TAC; −73.0%). This last manoeuvre was preceded by changes in the pressure overload induced transcriptional program as analysed by RNA sequencing. Genes encoding specific collagens, the Mef2 target myomaxin and the gene encoding the mechanosensitive channel Piezo2 were up-regulated after TAC in wild type but not in TRPC1/C4-DKO hearts. Conclusions: Deletion of the TRPC1 and TRPC4 channel proteins protects against development of pathological cardiac hypertrophy independently of the genetic background. To determine if the TRPC1/C4-dependent changes in the pressure overload induced alterations in the transcriptional program causally contribute to cardio-protection needs to be elaborated in future studies.